6. A CASE OF HUMAN IMMUNODEFICIENCY VIRUS PRESENTING WITH ALK-NEGATIVE ANAPLASTIC LARGE CELL LYMPHOMA, WITH POSITIVE EPSTEIN-BARR VIRUS EXPRESSION. (February 2015) - Bennett, J.; Ramuz, O.
Abstract : Background: Anaplastic large cell lymphoma (ALCL) is a mature T-cell lymphoma which is sub-classified into ALK-positive and ALK-negative primary systemic variants, and thirdly primary cutaneous anaplastic lymphoma. In the current WHO classification, ALK-negative ALCL is included as a provisional separate entity, occurring most commonly in elderly men and carrying a poor prognosis. Both ALK-positive and negative ALCL in the general population have been reported to be consistently negative for Epstein-Barr virus (EBV) expression. Case: A 40 year-old woman presented to a regional Queensland hospital with a recent history of weight loss, sweats, cough and right neck swelling. An axillary lymph node biopsy was performed as a part of a broad work-up. Histology revealed a lymphoproliferative tumour consisting of sheets of non-cohesive large atypical cells, with multi-lobate nuclei, and frequent mitoses. Immunohistochemical staining was positive for CD45, CD30, CD4, CD43 and EBER-ish; and negative for S100, pan-cytokeratin (AE1/AE3), CD20, CD79a, CD138, CD2, CD3, CD5, CD8, CD15, PAX5 and ALK1. Concurrent pathology investigations subsequently revealed that the patient was in fact HIV positive, and thus these findings were in keeping with a HIV-associated ALK-negative anaplastic large cell lymphoma. Discussion: Despite a paucity of reported cases, there is growing recognition of a unique HIV-associated ALCL which arises in the setting of immunosuppression. A small case series published in 2010 analysed 37 cases and found: an average age of 38 years; a male to female predominance of 4:1; a majority of cases were ALK-negative; one third showed positive EBV expression; and there was a variable loss of T-cell markers. This case represents another extremely rare example of HIV-associated ALCL, with positive EBV expression.